Small hepatitis B virus surface antigen promotes malignant progression of hepatocellular carcinoma via endoplasmic reticulum stress-induced FGF19/JAK2/STAT3 signaling. (28th February 2021) - Wu, Shuxiang; Ye, Shuangshuang; Lin, Xiaohan; Chen, Yan; Zhang, Yi; Jing, Zhentang; Liu, Wei; Chen, Wannan; Lin, Xinjian; Lin, Xu
Abstract: Chronic hepatitis B virus (HBV) infection is one of the major global health problems. Although the small protein of hepatitis B virus surface antigen (HBsAg), SHBs, is the most abundant HBV viral protein, its pathogenic role and molecular mechanism in malignant progression of HBV-related hepatocellular carcinoma (HCC) remain largely unknown. Here we reported that SHBs expression induced epithelial-mesenchymal transition (EMT) process in HCC cells and significantly increased their migratory and invasive ability as well as metastatic potential. Mechanistically, SHBs expression in HCC cells induced endoplasmic reticulum (ER) stress that activated the activating transcription factor 4 (ATF4) to increase the expression and secretion of fibroblast growth factor 19 (FGF19). The autocrine released FGF19 in turn activated JAK2/STAT3 signaling for induction of EMT process in HCC. Notably, SHBs was positively correlated with the expression of mesenchymal markers, the phosphorylation status of JAK2 and STAT3 as well as FGF19 levels in human HCC samples. HCC patients with SHBs positive had a more advanced clinical stage and worse prognosis. These results suggest an important role of SHBs in the metastasis and progression of HCC and may highlight a potential target for preventive and therapeutic intervention of HBV-related HCC and its malignant progression. Highlights: SHBs induces EMT of HCC cells to promote their invasion and metastasis. SHBs induces ER stress to activate transcription factor ATF4 for FGF19 upregulation. SHBs enhances secretion of FGF19 that binds to FGFR4 to activate JAK2/STAT3 axis. SHBs correlates with EMT and FGF19/JAK2/STAT3 signaling activation in HCC tissues. HCC patients with SHBs positive had a more advanced clinical stage and worse prognosis.